1989
DOI: 10.1016/s0006-3495(89)82888-7
|View full text |Cite
|
Sign up to set email alerts
|

Repulsive interactions between uncharged bilayers. Hydration and fluctuation pressures for monoglycerides

Abstract: Pressure versus distance relations have been obtained for solid (gel) and neat (liquid-crystalline) phase uncharged lipid bilayers by the use of x-ray diffraction analysis of osmotically stressed monoglyceride aqueous dispersions and multilayers. For solid phase monoelaidin bilayers, the interbilayer repulsive pressure decays exponentially from a bilayer separation of approximately 7 A at an applied pressure of 3 x 10(7) dyn/cm2 to a separation of approximately 11 A at zero applied pressure, where an excess wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 30 publications
(55 reference statements)
4
40
1
Order By: Relevance
“…Theoretical treatments (11,13,23) have indicated that the undulation pressure should extend the range of the underlying repulsive pressure (in this case the hydration pres sure), as shown experimentally in Figure 4. This behavior is also ob served between monoglycerides whose bending moduli differ greatly (56). However, because the data for liquid crystalline bilayers such as EPC ( Figure 2) can be fit to a single exponentionai of dr > 5 A , ex tracting information about the undulation pressure from a single data set is very difficult.…”
Section: Phosphorylcholine-containing Phospholipids' Phosphatidylchomentioning
confidence: 88%
“…Theoretical treatments (11,13,23) have indicated that the undulation pressure should extend the range of the underlying repulsive pressure (in this case the hydration pres sure), as shown experimentally in Figure 4. This behavior is also ob served between monoglycerides whose bending moduli differ greatly (56). However, because the data for liquid crystalline bilayers such as EPC ( Figure 2) can be fit to a single exponentionai of dr > 5 A , ex tracting information about the undulation pressure from a single data set is very difficult.…”
Section: Phosphorylcholine-containing Phospholipids' Phosphatidylchomentioning
confidence: 88%
“…The simulations were carried out in excess water, which denotes a bilayer containing more water molecules than the minimal amount needed for hydration. For a POPC bilayer, a minimal amount of ~9.5 water molecules per lipid are needed for hydration at 93% relative humidity (Mihailescu et al unpublished and 35,36 ) In these simulations, water-lipid ratios of 44.8 and 44.1 were used for POPC and DOTAP, respectively. The sequence of the capped S4mut peptide in our simulations is similar to the wild-type S4:…”
Section: Methodsmentioning
confidence: 99%
“…The data used in this paper have been previously published (4,6,20,23,24) and hence the methods will be described briefly. The lipids used were egg phosphatidylcholine (EPtdCho), E-PtdCho/cholesterol of various mole ratios, and dipalmitoylphosphatidylcholine (Pam2-PtdCho).…”
Section: Methodsmentioning
confidence: 99%